TRANSPARENCY OF THE INVESTMENT POTENTIAL OF THE UKRAINIAN ECONOMY IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT - Лісняк, Сергій Іванович; Пузирьова, Поліна Володимирівна (Journal of Strategic Economic Research, 2024)
The article considers the transparency of the investment potential of the national economy in the context of sustainable development. Approaches to understanding the concept of the investment potential of the national economy are studied, which differ depending on the chosen methodology, purpose and context in which the analysis is carried out (classical economic, behavioral, institutional, innovative and systemic approaches). It is established that the investment potential of the economy includes a set of resources, conditions and opportunities for investment activity, which enhances the ability of the economy to attract and effectively use investments in order to achieve long-term economic growth and improve the welfare of the population. The author identifies the main key factors of investment potential, which in synergistic interaction form the potential of the general economic level (economic resources; institutional conditions; human capital; technological level of development; social and environmental conditions). It is proved that the elements of investment potential are of particular importance in the context of sustainable development, which involves ensuring long-term economic growth without harming the environment and society. In determining the structure of investment potential, it is established that the investment potential of the national economy is a set of resources, opportunities and conditions that ensure the possibility of economic development through the attraction and efficient use of investments, where the main structural elements of investment potential are: financial potential, natural potential, labor potential, innovation potential, technological potential, infrastructure potential, institutional potential, socio-economic potential, environmental potential, and economic and social potential. The study of investment potential in the context of sustainable development found that the main factors are: environmental investments; social investments; innovative investments. Because of the study, the main directions of development of the investment potential of Ukraine in the context of sustainable development are proposed: reforming the legislative framework; development of financial markets; innovation policy; environmental policy; social investments. It is substantiated that in the context of global changes, it is necessary to ensure institutional stability, stimulate innovation and promote the development of a “green” economy, the implementation of which will increase Ukraine’s competitiveness in the world market and ensure long-term economic growth in compliance with the principles of sustainable development. The author proves that investment potential is a key driver for economic growth in any country, especially in the context of globalization, where sustainable development sets new requirements for investment activities, in particular, the balance between economic, social and environmental aspects.